INFLUENCE OF THE QUALITY OF MC.GAZINE TOWARDS STUDENTS READING INTEREST OF SMA NEGERI 3 MAGELANG - Fairiza Insani Zatika; Subhan Afifi; Kurnia Arofah (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2017)
The students of SMA Negeri 3 Magelang have low interest in reading to their own printed media, that is Mc.Gazine. The low reading interest affected by several factors, one of them is the quality of the product. Therefore, this research aims to figure out the influence of the quality of Mc.Gazine towards students’ reading interest of SMA Negeri 3 Magelang. The method used in this research was quantitative survey. The sample taken was approximately 35% of the whole population. Data collection applied in this research was questionnaire. Validity and reliability test were used to test the items in the questionnaire. Meanwhile, the data were analyzed using product moment Pearson correlation and simple linear regression. The results of the research were elaborated using S-O-R (Stimulus-Organism-Respond) Theory and Uses and Gratification Theory. To describe the results of the research, it was found out that the quality of school magazine Mc.Gazine towards students’ reading interest was at the medium state or category. It can be concluded that both variables i.e independent and dependent, have strong relationship. It is proven by the correlation coeficient value at 0,624 nearly to 1. On the other hand, the quality of Mc.Gazine (variable X) has positive significant influence towards the reading interest of the students of SMA Negeri 3 Magelang (variable Y) with the value at 0,000 < 0,05. Then, it was also found out that variable X gave contribution for approximately 39% on variable Y, therefore, the equation will show that when the variable contribution of variable X increases, then variable Y follows.